Single-Cell Transcriptomic Atlas of the Human Endometrium During the Menstrual Cycle. Issue 2 (February 2022) - Wang, Wanxin; Vilella, Felipe; Alama, Pilar; Moreno, Inmaculada; Mignardi, Marco; Isakova, Alina; Pan, Wenying; Simon, Carlos; Quake, Stephen R.
Abstract : (Abstracted from Nat Med 2020;26:1644–1653) The monthly remodeling, shedding, and regeneration of the endometrium defining the human menstrual cycle is driven by gene expression changes in the underlying tissue hierarchy. Significant heterogeneity exists among cell types in the endometrium, such that multiple cell types vary dramatically in state through a monthly cycle and undergo various forms of differentiation at rapid rates.